PENGARUH TINGKAT KEDISIPLINAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR FIQIH DI MTS AL-MUSHLIHIN KECAMATAN BINJAI KOTA KOTA BINJAI - Rois Ridho Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to determine the magnitude of the relationship level of discipline and learning motivation with the results of learning jurisprudence MTs Al-Mushlihin Binjai, either individually or collectively. The population in this study is all students of MTs Al-Mushlihin Binjai amounted to 546 people in 2016/2017. The sample of this study is set at 85 people. The data collection tool used questionnaires in the form of Likert scale (for the variable of discipline and learning motivation) and test question for student learning result variable. Questionnaires are arranged based on indicators of variables and examined to the supervisor of the thesis, then tested to the respondent not the research sample. After instrument test, it is known that all instrument of variable X1 consist of 34 items and 30 valid items and X2 variable consist of 34 items and 31 valid. Variable Y uses test questions. Test data variable analysis requirements X1, X2, and Y note that all normal distributed variables so that linearity test can be tested and linearity test results were regression between variables X1 with Y and X2 with Y also linear with p value <0.05. The results showed that the level of discipline and motivation to learn has a significant relationship with the results of learning jurisprudence. In test of research hypothesis, obtained correlation X1 with Y = 0.53, correlation X2 with Y = 0.24. Correlations X1 and X2 together with Y of = 0.39